Fatores associados à hospitalização na Chikungunya - Lopes, Danielle Torres dos Santos (2022)
Introduction: Chikungunya is a disease caused by the RNA virus Chikungunya (CHIKV), of the genus Alphavirus, family Togaviridae, transmitted to humans through the bite of infected female mosquitoes of the species Aedes aegypti and Aedes albopictus. It manifests itself in an acute febrile form, with symptoms similar to those of other arboviruses. Autochthonous transmission of CHIKV has already been reported in 114 countries and the annual estimate of cases ranges from 52,774 to 328,943. Hospitalization is uncommon in cases of Chikungunya and there are gaps in knowledge about the factors associated with this outcome. Objective: The present study evaluated factors associated with hospitalization in patients with acute CHIKV infection. Method: A cross-sectional study was carried out, including data from cases of the acute form of Chikungunya fever with laboratory confirmation in residents of the municipality of Vitória, state of Espírito Santo, Brazil, which occurred between 2016 and 2020, and accessed through the databases of the Notifiable Diseases Information System and eSUS Health Surveillance. Results: 2,868 patients were included, of which 1.42% (n = 41) were hospitalized. There was a difference in terms of age between hospitalized and non-hospitalized patients, which was smaller in hospitalized patients (median = 26 years, interquartile range = 12 - 61) than in non-hospitalized patients (median = 47 years, interquartile range = 34 - 59) (p -value = 0.001). Pregnancy was significantly longer in hospitalized patients (n = 2, 10.5%) than in nonhospitalized patients (n = 36, 2.0%) (p-value = 0.010). As for clinical manifestations, some symptoms were significantly less frequent among hospitalized patients, such as myalgia (pvalue = 0.006), headache (p-value < 0.001), nausea (p-value = 0.009), back pain (p-value < 0.001), arthritis (p-value = 0.014), arthralgia (p-value < 0.001) and retro-orbital pain (p-value < 0.001). There was no statistically significant difference between the groups in terms of gender, with greater involvement of women among hospitalized (n = 26) and non-hospitalized (n = 1,910) (p-value = 0.573), in addition to pre-existing diseases, and time disease evolution (p-value = 0.102). Back pain (OR = 0.134; 95% CI = 0.044 - 0.409) and arthralgia (OR = 0.226; 95% CI = 0.083 - 0.613) were protective predictors of hospitalization. Conclusion: The study demonstrated that milder clinical manifestations in the acute phase of Chikungunya fever were identified among hospitalized patients, and some signs and symptoms were protective predictors of hospitalization. Therefore, understanding the correlation between sociodemographic characteristics, comorbidities and symptoms presented by individuals affected by the disease allows the development of measures for effective prevention, control and management of the disease, reducing hospitalizations